2015
DOI: 10.1074/jbc.m115.636563
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Phosducin and Its Complex with the 14-3-3 Protein

Abstract: Background: Phosducin is a conserved regulatory phosphoprotein involved in phototransduction whose function is regulated in a 14-3-3-dependent manner. Results: The 14-3-3 protein binding affects the structure and the accessibility of several regions within both domains of phosphorylated phosducin. Conclusion: The 14-3-3 protein sterically occludes the whole G t ␤␥ binding interface of phosducin. Significance: Mechanistic explanation is given for the 14-3-3-dependent inhibition of phosducin function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Here, control of subcellular localization, enzymatic activity, and biological half-life can be envisioned as modes by which 14-3-3 PPI modulators could act, e.g., on transcription factors (YAP, c-Jun, MLF1, FOXOs), enzymes shuttling between cytoplasm and nucleus (Cdc25 phosphatases, HDACs), or kinases (B, C-Raf, LRRK2). In recent years, a growing number of crystal structures of 14-3-3 in complex with different binding partner motifs have been published, for example, the cystic fibrosis ion channel CFTR, 55 the small heat shock protein HSPB6, 56 phosducin, 57 and the Parkinson's disease-related kinase LRRK2. 58 As dimeric species that dock onto pairs of specific phosphorylated serine-or threonine-containing motifs, 14-3-3 proteins are endowed with special signaling, mechanical, and evolutionary properties.…”
Section: Intentionally Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, control of subcellular localization, enzymatic activity, and biological half-life can be envisioned as modes by which 14-3-3 PPI modulators could act, e.g., on transcription factors (YAP, c-Jun, MLF1, FOXOs), enzymes shuttling between cytoplasm and nucleus (Cdc25 phosphatases, HDACs), or kinases (B, C-Raf, LRRK2). In recent years, a growing number of crystal structures of 14-3-3 in complex with different binding partner motifs have been published, for example, the cystic fibrosis ion channel CFTR, 55 the small heat shock protein HSPB6, 56 phosducin, 57 and the Parkinson's disease-related kinase LRRK2. 58 As dimeric species that dock onto pairs of specific phosphorylated serine-or threonine-containing motifs, 14-3-3 proteins are endowed with special signaling, mechanical, and evolutionary properties.…”
Section: Intentionally Targetingmentioning
confidence: 99%
“…59,60 14-3-3 binding sites lie within motifs that are phosphorylated by basophilic protein kinases such as PKB/Akt, p90RSK, PKA, and AMPK. 57 This means that 14-3-3 affinity capture and quantitative mass spectrometry procedures can be used to identify targets of, for example, regulation by insulin, growth factors, energy stress, and adrenalin that activate these respective kinases. In this way, new 14-3-3-based mechanisms have been identified to explain how insulin and growth factors regulate synchronized shifts in glucose uptake, glycolysis, mTORC1 signaling, protein translation, and other regulatory events that promote cell growth and proliferation.…”
Section: Intentionally Targetingmentioning
confidence: 99%
“…Therefore, it is unlikely that phosphorylation alone interferes with GCAP2 binding to RetGC in vitro or in vivo . However, we have shown that phosphorylation at Ser201 triggers 14-3-3 binding to GCAP2 in vivo 41 , an step that could conceivably hinder GCAP2 binding to RetGC, in a similar way as 14-3-3 binding to phosphorylated phosducin masks its binding sites to Gβγ 62 , 63 .…”
Section: Discussionmentioning
confidence: 86%
“…Although not directly compared, less 14-3-3 isoform selectivity would therefore be expected for serotonin N-acetyltransferase. The 14-3-3 target proteins RGS3 and phosducin show interactions outside the binding groove, in a less conserved area of 14-3-3 (Kacirova et al 2015 ; Rezabkova et al 2011 ). For neither RGS3 nor phosducin the binding affinities to the different 14-3-3 isoforms have been compared, although RGS3 is reported to interact with 14-3-3β and τ in addition to 14-3-3ζ (Benzing et al 2000 ; Niu et al 2002 ; Rezabkova et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%